BIOACTIVE AND OTHER PIPERIDINE ALKALOIDS FROM CASSIA-LEPTOPHYLLA - Bolzani, Vanderlan da Silva [UNESP]; Gunatilaka, AAL; Kingston, DGI (Elsevier B.V., 1995)
Four new piperidine alkaloids, leptophyllin A (4), 3-acetylleptophyllin A (5), leptophyllin B (8), and (-)-spectaline (1), and 3 known piperidine alkaloids, (-)-spectalinine (2), canavaline (3), and iso-6-canavaline (7), were isolated by a bioassay-guided fractionation of a leaf extract of Cassia leptophylla. The alkaloids 1 - 3 were active in a mechanism-based DNA-modifying yeast assay and 2 was moderately active in Vero monkey and Chinese hamster ovary cell cytotoxicity assays.